Factors Related to Work Stress among Health Office Employees during Covid-19 Pandemic - Luga Rizqi Cristenzein; Kadek Tresna Adhi (Universitas Airlangga, 2021)
Introduction: Study related to work stress is usually more focused on the industrial sector. Meanwhile, workers in other sectors such as the government organization also have the potential to feel stressed due to their job. During the COVID-19 (Coronavirus Disease) pandemic, Health Office is one of the main stakeholders in handling and preventing COVID-19. The COVID-19 pandemic can cause work stress due to unachieved health programs and huge demands to develop programs related to this pandemic. This study analyzed the relationship between individual factors, work factors, and factors outside of work with level of work stress among Health Office employees. This study is expected to be able to analyze work stress and its determinant as early as possible. Methods: This study was a cross-sectional study using the Depression, Anxiety, Stress Scale 42 (DASS-42) and NIOSH (National Institute for Occupational Safety and Health) Generic Job Stress Questionnaire instrument. This study was conducted at the Public Health Office Bogor Regency April 2021. This study used total sampling method on employees of the Public Health Office Bogor Regency with total sample collected of 135 respondents. Data analysis in this study was performed using multiple logistic regression. Results: 86.67% of respondents did not experience work stress, 5.93% of respondents had mild work stress, and 7.41% of respondents experienced moderate work stress. Moreover, workload (p = 0.0001) and social support (p = 0.011) had a significant relationship in increasing work stress. Conclusion: Workload was the most dominant variable affecting work stress in which workers who had high subjective workload were 33.63 times more stressful compared to workers who had the appropriate workload. Prevention of occupational stress can be done by adjusting workloads and building a good social environment between colleagues.Keywords: factors outside of work, health office, individual factors, work factors, work stress